Selection of Appropriate Semiconductor Switches for Induction Heated Pipe-Line using High Frequency Full Bridge Inverter - Pradip Kumar Sadhu; Debabrata Roy; Nitai Pal; Sourish Sanyal (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
An exhaustive method for the choice of different power semiconductor switches for high frequency full bridge inverter fed induction heater is presented. Heating coil of the induction heater is made of litz wire which minimises the skin effect and proximity effect at high operating frequency. With the calculated optimum values of inductance and resistance of heating coil at a particular operating frequency, high frequency full bridge inverter topology has been simulated using P-SIM software as well as constructing the experimental model of same rating. Obtained the voltage waveforms across heating coil and current waveforms through it, have been taken for further analysis. From this analysis selection of suitable power semiconductor switches like IGBT, GTO and MOSFET are made. Waveforms have been shown to justify the feasibility for real implementation of high frequency full bridge inverter fed induction heater in industrial applications.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.6108